3D printing and modelling of continuous carbon fibre reinforced composite grids with enhanced shear modulus. (1st July 2023) - Chen, Yuan; Klingler, Andreas; Fu, Kunkun; Ye, Lin
Highlights: Continuous carbon fibre (CCF) reinforced polyamide (PA) composite grids with enhanced shear elastic modulus are topologically-tailored and fabricated by 3D printing. A new numerical scheme is proposed to predict the elastic responses and behaviours of 3D printed CCF/PA composite grids with complex fibre paths. Specific shearing test method is established and implemented, An effective index is proposed for evaluating the CCF reinforcement efficiency independent of the reinforced structures. Abstract: Within this research, continuous carbon fibre (CCF) reinforced polyamide (PA) composite grids were topologically-tailored and 3D printed to show enhanced shear modulus. Based on the 3D printing trajectories, a new numerical scheme to predict the elastic responses and behaviours of the 3D printed CCF/PA composite grids was developed. To verify the design and the numerical model, specifically created shearing tests were performed. By comparison, the modelled data agrees well with the experiments. Reinforced by CCFs, the effective shear modulus of 3D printed PA specimens was found to increase by 641.3%, 437.6% and 723% for basic structural configurations with material volume fractions of 20 vol-%, 40 vol-% and 60 vol-%, respectively. Even more, an index for evaluating the CCF reinforcement efficiency, independent of the design of the reinforced structure, was proposed and applied, indicating that the effective shear modulus can be maximally enhanced by 40.5 MP once the CCF volume content is increased by 1%. This study innovatively provides a systematic approach by integrating topological design, modelling and experimental methods for creating engineering grid structures with enhanced shear modulus, and thus proving the efficiency of using continuous fibres as structural reinforcements in 3D printing for engineering applications.